UNDERSTANDING INDIVIDUAL ADULTS AS THE BASIS FOR SOCIAL ORDER CHANGE - Singgih Prastawa; Kevin Tony Rey; Satria Omega Kadun (PT. Intelek Cendikiawan Nusantara, 2024)
In general, an adult individual is a person who has completed for himself which includes cognitive, affective and psychomotor. This makes adult individuals can be the basis for changes in social order. This paper analyzes adult individuals who have a clear personality and occupation and it confirms that such adult individuals can be the basis or foundation for social transformation to occur. Social transformation requires a clear foundation because the process of change itself has a continuous nature for the better. The basis of social transformation is not given to those adults who are emotionally and intellectually unstable or given to those individuals who are still in the process of growing and developing. The individual adult on whom social change is based is capable of making decisions and taking responsibility for them. This paper seeks to provide an understanding of the individual adult who is the basis or foundation of social transformation. The mature personality aspects of the adult individual and his/her work are considered to be the basis for changing the social order for the better.